Student satisfaction assessment using Servqual approaches in receiving banking services - Novi Primita Sari (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
Customer satisfaction is one of the important assessment indicators that cannot be ignored in every service activity, especially in the business world, which is centered on service activities, one of which is the banking world. In this study, we try to focus on assessing the satisfaction of banking services obtained by students of the University of Muhammadiyah Malang in the administration of lecture payments. This research is explanatory using quantitative data obtained with primary data through the distribution of questionnaires distributed to students who happen to be at the location and are conducting transactions. The sample used was 50 students taken accindental. By using the SERVQUAL approach and CARTER dimension methods to then be analyzed using the ordinary panel data regression method to find out which of the 6 dimensions have the most powerful influence on the assessment of service satisfaction obtained by students.